Wading Birds of Northern Belize - Justin Dalaba; Venetia S. Briggs-Gonzalez; Jorge Eduardo Ruano; Frank J. Mazzotti (EDIS)
Belize is home to over 605 bird species, many of them wading birds popular with bird watchers who enjoy their bright colors and charismatic behavior. Bird-watching is a major contributor to successful wildlife conservation and is important as native habitat loses ground to development. This 4-page fact sheet written by Venetia S. Briggs-Gonzalez, Jorge E. Ruano, Justin R. Dalaba and Frank J. Mazzotti and published by the UF/IFAS Department of Wildlife Ecology and Conservation presents photos and descriptions that will help identify some common and some rare wading birds. https://edis.ifas.ufl.edu/uw469